Harnessing Sustainable Energy: Pico-Hydro Power Generation Using an Undershoot Water Wheel Turbine in Irrigation Canals - Iftitah Imawati; Galang Ismu Kurniawan; Muhammad Rifan Ghifari; Muhammad Nauval; Fajar Arisandi; Husein Mubarok; Hendra Setiawan (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
With the increasing demand for electricity and environmental concerns related to the use of fossil fuels, the need for renewable energy solutions is becoming increasingly important. The potential of hydropower generation needs to be harnessed for daily electricity needs. The proposed system harnesses the flow of water in irrigation channels, using turbines made of galvanized plates and plastic to generate electricity for small-scale applications such as street lighting. To overcome the challenges of manual monitoring, especially during the rainy season, an IoT-based monitoring tool is included. This tool allows remote tracking of system performance, including generator output, battery voltage, and load current, through an internet-connected smartphone interface, allowing for real-time monitoring. Laboratory and field tests were conducted in Yogyakarta, Indonesia. The system demonstrated the ability to produce stable voltage and power, achieving an efficiency of 11.38%. The system demonstrated a data transmission delay of 5.64 seconds via Blynk, with a recorded power consumption of 2,231 watts. The sensor readings showed high accuracy, with generator voltage accuracy of 99.33% and load current accuracy of 99.26%.